Providing Slow Stroke Back Massage Intervention to Reduce Headache in Hypertension Patients - Hasim, Ely; Khotimah, Husnul; Hafifah, Vivin Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
often occurs in people aged 40 – 69 years, characterized by an increase in blood pressure that exceeds 140/90mmHg. The elderly are the age most likely to experience hypertension because at this age the blood vessels will experience hardening, this will cause the heart to clot blood more strongly which ultimately results in hypertension in the elderly. Objective: Implementing the Slow Stroke Back Massage intervention to reduce hypertension pain in the elderly Method: Using experimental methods, interviews and physical examination, Results: This case description shows that after the slow stroke back massage technique intervention was carried out the level of headache in the patient's hypertension decreases. Conclusion: Based on the results of the case evaluation obtained in patients who were given Slow Stroke Back Massage therapy to the elderly Mrs. M has been implemented and proven to be effective in treating the problem of back headaches with hypertension).